Engineering tumor-oxygenated nanomaterials: advancing photodynamic therapy for cancer treatment - Zuo, Tingting; Li, Xiaodie; Ma, Xuan; Zhang, Ye; Li, Xueru; Fan, Xuehai; Gao, Mingze; Xia, Donglin; Cheng, Huijun (Frontiers in Bioengineering and Biotechnology, 2024)
Photodynamic therapy (PDT), a promising treatment modality, employs photosensitizers to generate cytotoxic reactive oxygen species (ROS) within localized tumor regions. This technique involves administering a photosensitizer followed by light activation in the presence of oxygen (O2), resulting in cytotoxic ROS production. PDT's spatiotemporal selectivity, minimally invasive nature, and compatibility with other treatment modalities make it a compelling therapeutic approach. However, hypoxic tumor microenvironment (TME) poses a significant challenge to conventional PDT. To overcome this hurdle, various strategies have been devised, including in-situ O2 generation, targeted O2 delivery, tumor vasculature normalization, modulation of mitochondrial respiration, and photocatalytic O2 generation. This review aims to provide a comprehensive overview of recent developments in designing tumor-oxygenated nanomaterials to enhance PDT efficacy. Furthermore, we delineate ongoing challenges and propose strategies to improve PDT's clinical impact in cancer treatment.